Experimental assessment of condition monitoring techniques for an OWC electrical generator operating at overload - Joseba Lopez-Mendia; Iker Erkiaga; Pablo Ruiz-Minguela; Ivan Ruibal; Eider Robles; Salvador Ceballos (Energy Conversion and Management: X, 2025)
Traditionally, the nominal power of a generator in renewable energy converters is determined based on its maximum mechanical input power within the drive train. Implementing this procedure for Wave Energy Converters would result in a generator operating well below its nominal power, leading to prolonged periods of suboptimal efficiency depending on the location of the device.Generators are generally engineered to manage brief periods of overload. Consequently, opting for a smaller generator and permitting it to function above its nominal power can be a viable strategy. However, it is essential to carefully evaluate the limits and operational durations specific to each application. Enhancing the operational speed may result in increased vibrations, while boosting the torque can elevate the temperature of the stator winding. This temperature rise can eventually compromise the insulation of the stator winding, leading to potential failure.At the present work, an overload operational regime of a generator, under the special operation mode of the MARMOK-Idom Oscillating Water Column (OWC) Wave Energy Converter (WEC), will be evaluated at overload till the end of its life. The testing procedure uses an “accelerated testing” concept, introducing consecutive representative power peaks instead of real wave trains, reflecting the probable mechanical power peak magnitudes and durations to simulate real conditions. Several generator condition monitoring alternatives will be evaluated to identify the best option to detect and predict a future failure of the generator stator winding, such as Electrical Signature Analysis, Park’s Vector Approach, or direct monitorization of stator temperature and insulation. Through an appropriate condition monitoring technique, a stator winding degradation model will be developed, which could assist in the sizing phase of the generator’s nominal power in future designs, as well as in making decisions to modify the control law based on the degradation of the generator during the operation of the wave energy converter.